Pembelajaran Pendidikan agama Islam dalam membentuk karakter religius siswa di Mts Ma'arif Giwangretno Kebumen - Mohamad Choerul Subchi; Nurhidayah Nurhidayah; Nihayatul Husna (IAINU Kebumen, 2023)
The formation of religious character has become an important issue in the world of education lately, this is related to the phenomenon of moral decadence that occurs in the midst of this nation's young generation which is increasing and diverse. The role of religious education, especially Islamic religious education, is very strategic in realizing the formation of students' religious character. The implementation of religious education learning in schools can be internalized in intra and extra school activities and prioritizes the application of religious teachings in daily life. This is also what MTs Ma'arif Giwangretno Kebumen implements as a formal educational institution. The results of this study conclude that the implementation of Islamic religious education learning in shaping the religious character of students at MTs Ma'arif Giwangretno Kebumen is good, where in PAI learning activities have carried out careful planning stages which aim to facilitate the course of learning activities / programs, carry out the learning process PAI through intracurricular and extracurricular with several learning methods as well as conducting program evaluations. The model in learning Islamic religious education at MTs Ma'arif Giwangretno Kebumen uses the PAIKEM method. This is because it will make learning more varied so that the learning process in class will be more interesting and fun.